The literacy secondhand bookstore / Widya Hana Nurulhuda Mohd Salihin … [et.al.]. - Mohd Salihin, Widya Hana Nurulhuda; Johnichal Rayong, Joanna; Busari, Ummaira Nurfazillah; Edwin, Rachel (2013)
The name of our company is The Literacy Secondhand Bookstore. This business is in the form of partnership which consists of four partners. All of the partners agreed to give the name of the company as The Literacy Secondhand Bookstore. Literacy means the condition or quality of being literate especially the ability to read and write. Secondhand bookstore where we offer secondhand books to customers. The combination of the Literacy Secondhand Bookstore means we offer secondhand books to customers and our bookstore will make customers gain knowledge and the quality of being literate. Secondhand books are affordable and many customers want to buy books at cheaper price and this is where we play our role as a secondhand bookstore.